Al-Khawarizmi dan Warisan Ilmiahnya: Membangun Dasar-Dasar Komputasi Yang Kita Kenal Hari Ini - Hardika Saputra (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Al-Khawarizmi, a Muslim scholar in the 9th century, has had a significant impact on the development of modern science and technology, particularly in the fields of mathematics and computing. Through his works in algorithms, algebra, and geometry, Al-Khawarizmi revolutionized the solution of complex and difficult mathematical problems, helping to lay the foundation for the development of modern computer technology. This research employs a qualitative research method with a literature review design. A literature review involves the collection, analysis, and evaluation of previous sources related to the research topic, including published journals, books, reports, and other online sources. Findings and discussions indicate that Al-Khawarizmi plays an important role in the current development of computer technology. His discoveries, such as algorithms and the concept of zero, have become fundamental in computer science. This underscores that the contributions of Al-Khawarizmi have played a key role in the evolution of modern computer technology.